ECONOMIC CONSIDERATIONS IN ANCIENT CHINA - Kamolov, Dostonbek; Ropiyeva, Feroza (Science technology&Digital finance, 2023)
This article covers extensively what ideas and propaganda were carried out in ancient China, the propaganda and content of the economic ideas of Confucius, the legists, Syun-Szi, Guan-szi, and how they were applied to the government.